Experimental study of enhancement of heat transfer and pressure drop in a solar air channel with discretized broken V-pattern baffle. (February 2017) - Kumar, Raj; Sethi, Muneesh; Chauhan, Ranchan; Kumar, Anil
Abstract: This article presents an experimental study on heat transfer and friction characteristics of solar air channel fitted with discretized broken V-pattern baffle on the heated plate. The effect of geometrical parameters, predominantly the gap width and gap location has been investigated. The roughened baffle air channel has a width to height ratio, W/H of 10. The relative baffle gap distance, Dd /Lv and relative baffle gap width, gw /Hb has been varied from 0.26 to 0.83 and 0.5–1.5, respectively. Experiments have been carried out for the range of Reynolds number, Re from 3000 to 21, 000 with the relative baffle height, Hb /H range of 0.25–0.80, relative baffle pitch, Pb /H range of 0.5–2.5; and angle of attack, αa range of 30°–70°. The optimal values of geometrical parameters of roughness have been obtained and discussed. For Nurs the greatest enhancement of the order of 4.47 times of the corresponding data of the without channel has been obtained. The absolute highest data of thermal hydraulic performance parameter has been found to be greater corresponding to Dd /Lv of 0.67, gw /Hb of 1.0, Hb /H of 0.50, Pb /H of 1.5, and αa of 60°. The maximum value of the thermal hydraulic performance parameter was found to be 3.14 for the range of parameters investigated. Highlights: Article presents experimental investigation of discretized broken V-Pattern baffle solar air channel. Nusselt number, pressure drop and thermo-hydraulic performance are experimentally investigated. An optimum value of roughness parameters is determined on the basis of overall thermal performance.